Sosialisasi Penerapan Aplikasi Mobile Dalam Pembelajaran Bahasa Inggris Untuk Mahasiswa Sistem Informasi - Suerni; Eka Ramadhani Putra; Dinda Salsabila Ritonga (STIKES Columbia Asia Medan, 2023)
This study aims to analyze the socialization process of implementing a mobile application for English language learning among Information Systems students and to evaluate the effectiveness of the socialization. The research employs a descriptive qualitative method, collecting data through observation, interviews, questionnaires, and documentation. The subjects consist of 30 students purposively selected based on their interest and readiness to participate in the socialization. The socialization process includes material delivery, application demonstration, and brief training. Results show an increase in students’ positive perceptions regarding the ease of use and benefits of the application in supporting English learning. Additionally, students’ learning interest significantly improved after the socialization. The effectiveness evaluation reveals that the delivered material is easy to understand, and the interactive methods successfully engage student enthusiasm. The usage of the mobile application among students notably increased, both in terms of downloads and routine usage frequency. However, some challenges remain related to motivation for consistent application use, which should be addressed in future development and socialization efforts. This study recommends enhancing technical support and motivation strategies to encourage sustainable adoption. Thus, implementing mobile applications in English learning can be an effective alternative to improve learning quality in the digital era.